Monitoring races of Bremia lactucae in the State of São Paulo from 2003 to 2012 - Braz, L. T. [UNESP]; Diniz, G. M.M. [UNESP]; Castoldi, R.; Nunes, R. C. [UNESP]; Galatti, F. S. [UNESP]; Camargo, M. [UNESP]; Marin, M. V. [UNESP]; Dalpian, T.; Souza, J. O.; Gomes, R. F. [UNESP]; Rabelo, H. O. [UNESP] (International Society for Horticultural Science (ISHS), 2016)
Lettuce is one of the most widely cultivated leafy vegetables in Brazil, which encourages the increase in infestation of production areas by the phytopathogen Bremia lactucae Regel, the causative agent of mildew, making it one of the principal crop diseases. In view of the quantity of races adapted to growing regions, the objective of this work was to do a survey of the races of Bremia lactucae found in the state of São Paulo between 2003 and 2012. On the basis of the identification system sextet code in studies of races in 2003 and 2004 in São Paulo, we identified the first race of B. lactucae, designated SPBl:01. In surveys in 2006 and 2007, three new races were found, namely SPBl:02, SPBl:03, and SPBl:04. In 2008 and 2009, we noted the emergence of two more new races, SPBl:05 and SPBl:06. In 2010, 2011 and 2012, the monitoring of races in São Paulo made it possible to identify five more new races: SPBl:07, SPBl:08, SPBl:09, SPBl:10, and SPBl:11. For lines of lettuce to acquire resistance to all races of B. lactucae found up to 2012, the resistance factors RF-17, RF- 18, and RF-38 should be incorporated in these lines. According to monitoring, we can conclude that, from 2003 to 2012, there have been 11 races of B. lactucae that affect the productivity and quality of the lettuce crop in the state of São Paulo.
Keywords: Differentiating cultivars; Genetic improvement; Lettuce; Mildew; Resistance